The magnet design for the HLS storage ring upgrade project - 张浩 李为民 冯光耀 王琳 张善才 李为 梁军军 (Chinese physics C, 2012)
In order to improve the performance of the Hefei Light Source （HLS）,in particular to get higher brilliance synchrotron radiation and increase the number of straight section insertion devices,an upgrade project called HLSII will be launched soon.The storage ring lattice,which has a double bend achromatic structure with four periods,comprises eight dipoles,32 quadrupoles and 32 combined function sextupoles.The design and analysis of the magnets are shown in this paper,along with the optimization of the multipurpose combined function magnet,which consists of three magnets：skew quadrupole,horizontal dipole and vertical dipole,with the main sextupole magnet.This type of magnet is the first one that has been designed and used in China.The mechanical design and fabrication procedures for the magnets are also presented.